Constructed Wetlands for Pollution Control - Knight, R. (IWA Publishing, 2000)
The book presents a comprehensive up-to-date survey of wetland design techniques and operational experience from treatment wetlands. This book is the first and only global synthesis of information related to constructed treatment wetlands. Types of constructed wetlands, major design parameters, role of vegetation, hydraulic patterns, loadings, treatment efficiency, construction, operation and maintenance costs are discussed in depth. History of the use of constructed wetlands and case studies from various parts of the world are included as well. Constructed Wetlands for Pollution Control will be indispensable for wastewater treatment researchers and designers, decision makers in public authorities, wetland engineers, environmentalists and landscape ecologists. Contents Biological methods for the treatment of wastewaters Types of constructed wetland Aplications of the technology Framework for interpreting and predicting water quality improvement Mechanisms and results for water quality improvement Design Plants and planting System start-up Economics Case studies Scientific and Technical Report No.8